Osteogênese, vitamina A e anomalias esqueléticas em larva de Pacu, Piaractus mesopotamicus - Lopes, Taís da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Studies on skeletal anomalies in larvae and juveniles have been developed for several fish species commercially produced. The reason is because these anomalies cause many problems to aquaculture, such as increased production costs due to decreased survival, adverse effects on growth, decreased feed conversion, and increased susceptibility to diseases. The factors that determine the incidence of skeletal anomalies in fish larvae and juveniles are mainly nutritional, environmental and genetic. However, nothing is known about this subject in South American species, such as the pacu. Therefore, we aimed to describe the bone development of pacu; to evaluate the incidence of skeletal anomalies during larval development; to study the role of vitamin A in skeletal formation and the gene expression involved in this process, and to understand the turnover of vitamin A in bone and muscle tissues with the use of stable isotopes technique

Estudos sobre anomalias esqueléticas em larvas e juvenis têm sido desenvolvidos em várias espécies de peixes produzidas comercialmente. Isso porque o desenvolvimento ósseo anormal pode promover o aumento do custo de produção devido à diminuição da sobrevivência, efeitos negativos no crescimento, pior conversão alimentar, além do aumento da susceptibilidade à doenças. Os fatores causadores de anormalidades esqueléticas em larvas e juvenis de peixes são, principalmente, fatores nutricionais, ambientais e de origem genética. Porém, nada se sabe sobre esse assunto em espécies sul-americanas, como o pacu. Desta forma, o objetivo desta pesquisa foi descrever o desenvolvimento ósseo do pacu; avaliar a incidência de anomalias esqueléticas durante o desenvolvimento larval; verificar o papel da vitamina A na má formação esquelética e a expressão gênica envolvida nesse processo; e conhecer o turnover isotópico (13C) do tecido ósseo e muscular pela influência da vitamina A, com a utilização da técnica de isótopos estáveis
Keywords: Peixes; Pacu (Peixe); Animais - Anomalias; Ossos - Crescimento; Esqueleto; Vitamina A; Isótopos estáveis; Fishes